Sistematik Review: Faktor Resiko Obesitas terhadap Diabetes Mellitus Tipe 2 pada Remaja - Barto Mansyah (Jurnal Surya Medika (JSM), 2021)
Degenerative diseases or non-communicable diseases are caused by changes in lifestyle, especially changes in diet. One of the degenerative diseases is type 2 diabetes mellitus, characterized by insufficient insulin secretion, insulin resistance, and increased glucose production in the liver. Adolescence is a critical period, unhealthy dietary habits are one of the risky behaviors in adolescence, and an unhealthy diet in adolescents is one of the causes of obesity. Obesity is a hallmark of type 2 diabetes mellitus, and most adolescents with type 2 diabetes mellitus are obese at diagnosis. This study is a systematic review study with article search methodology through Google Scholar, PubMed, and Elsevier with the keywords Obesity as a Risk Factor for Type II Diabetes Mellitus in adolescents. There are 12 research articles identified. It is known that obsession in adolescents is a risk factor for diabetes mellitus—type 2 diabetes mellitus in adulthood. The importance of providing education that focuses on lifestyle changes that aim to reduce the level of overweight and obesity in children and adolescents as well as education is also given to all family members so that families understand the importance of lifestyle changes for the successful management of type 2 diabetes mellitus.